Electronic Administrative Judicial Procedure of Ukraine and the Right to Judicial Protection: Problems of Legal Regulation and Practical Issues - Oleksandr Shevchuk; Ihor Kompaniiets; Olena Volianska; Oleksandra Shovkoplias; Vasyl Baranchuk (Juridical Tribune - Review of Comparative and International Law, 2024)
The article deals with certain problems of legal regulation of electronic administrative judicial procedure in the context of the realization of the right to judicial protection. The methodological basis of a scientific article is a set of philosophical, general and special scientific methods. It is indicated that electronic administrative judicial procedure should be attributed to the components of electronic governance. It has been established that the right to appeal to an administrative court and ways to protect violated rights cannot be limited when submitting and considering electronic documents, since the lack of such an opportunity leads to a violation of fundamental human rights, court practice in this matter is given. It has been established that it is the application of a specific method of protecting participants in public law relations of a violated or denied right that is the result of the activity and effectiveness of the legal mechanism for protecting rights when using information and communication technologies in administrative courts. Revealed that these rights protection mechanisms should be applied on the basis of the rule of law, accessibility and transparency, impartiality and independence, including the principles of oral hearing and equality of arms. The analysis of the concepts "electronic justice", "electronic court" in the scientific literature, national and international legal documents is carried out. The essence of "electronic administrative judicial procedure", its elements, stages of implementation in practice are disclosed. Separate directions for improving the legal regulation of electronic administrative judicial procedure regarding the implementation of the right to judicial protection are proposed.